SISTEM PENDUKUNG KEPUTUSAN FOOD COMBINING DENGAN METODE FORWARD CHAINING - Salim, Inez Noviyanti; Budhi, Robby Kurniawan; Widianto, Yonatan (Jurnal Tr@nsForMat!ka, 2016)
Public awareness of healthy eating is increasingly formed.However, healthy eating knowledge possessed by each individual is still minimal. This decision support system will use forward chaining method to draw conclusions from the facts already known. Output from the application of this decision support system is the decision whether a food that will be consumed , either for combined or not. The purpose of this research is to create a decision support system of food combining with forward chaining method. This research is expected to help the user in decision making with regard healthy diet food combinations